2019
DOI: 10.1037/met0000215
|View full text |Cite
|
Sign up to set email alerts
|

Studying developmental processes in accelerated cohort-sequential designs with discrete- and continuous-time latent change score models.

Abstract: Studying the time-related course of psychological processes is a challenging endeavor, particularly over long developmental periods. Accelerated longitudinal designs (ALD) allow capturing such periods with a limited number of assessments in a much shorter time framework. In ALDs, participants from different cohorts are measured repeatedly but the measures provided by each participant cover only a fraction of the time range of the study. It is then assumed that the common trajectory can be studied by aggregatin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 70 publications
3
26
0
Order By: Relevance
“…Previous research has shown that, when the assumption of cohort equivalence is met and thus there are no cohort differences, the parameters of the generating process can be adequately recovered. For example, Estrada and Ferrer (2019) showed that, with sample sizes above 200 cases, the application of various ALD sampling schedules allowed recovering the parameters defining the population’s trajectory with a LCS model (McArdle, 2009). However, Estrada and Ferrer (2019) also found that, in the presence of cohort effects, several parameters defining key features of the population trajectory were recovered with substantial bias.…”
Section: Cohort Equivalencementioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that, when the assumption of cohort equivalence is met and thus there are no cohort differences, the parameters of the generating process can be adequately recovered. For example, Estrada and Ferrer (2019) showed that, with sample sizes above 200 cases, the application of various ALD sampling schedules allowed recovering the parameters defining the population’s trajectory with a LCS model (McArdle, 2009). However, Estrada and Ferrer (2019) also found that, in the presence of cohort effects, several parameters defining key features of the population trajectory were recovered with substantial bias.…”
Section: Cohort Equivalencementioning
confidence: 99%
“…For example, Estrada and Ferrer (2019) showed that, with sample sizes above 200 cases, the application of various ALD sampling schedules allowed recovering the parameters defining the population’s trajectory with a LCS model (McArdle, 2009). However, Estrada and Ferrer (2019) also found that, in the presence of cohort effects, several parameters defining key features of the population trajectory were recovered with substantial bias. This bias led to poor confidence interval coverage rates, and was found for parameters that differed across cohorts, and importantly, also for parameters that were cohort-invariant.…”
Section: Cohort Equivalencementioning
confidence: 99%
See 1 more Smart Citation
“…Many of the analytical methods discussed earlier with respect to limitations may well be appropriate for certain research projects. Researchers need not limit themselves to traditional longitudinal panel data, either: there are alternative collection modes, many of which may better "tap into" our phenomena of interest, that bear consideration in future research (e.g., accelerated cohort designs, intensive longitudinal design; see CTSEM discussion of such data in Estrada & Ferrer, 2019;Ryan et al, 2018). Moreover, the advent of continuous time meta-analysis (Dormann et al, 2019;Guthier et al, 2020) is an exciting recent development in this literature, and it stands to contribute to time-cognizant occupational health research designs, analyses, and practical applications moving forward.…”
Section: Caveats To Ctsemmentioning
confidence: 99%
“…This paper focuses on modeling retest in latent change score (LCS) models (McArdle, 2009). LCS models were developed explicitly to model data that follow exponential forms, and have been extensively used in the analyses of developmental data, especially cognitive abilities (Estrada et al, 2020;Estrada & Ferrer, 2019;Ferrer et al, 2007;Ferrer et al, 2010;Ghisletta & Lindenberger, 2003, 2005Grimm, 2008;Kievit et al, 2018;among others). LCS models offer a general framework, of which growth models such as a latent growth curve can be a special case.…”
Section: But Which Model Of Change?mentioning
confidence: 99%